Study about 4p and 4q Subtelomeric Microdeletion in De Novo Ring Chromosome 4 - Akbas, Halit; Cine, Naci; Erdemoflu, Mahmut; Atay, Ahmet Engin; Simsek, Selda; Balkan, Mahmut; Turkyilmaz, Aysegul; Fidanboy, Mehmet (New Horizons in Medicine and Medical Research Vol. 9, 2022)
Ring chromosomes are unusual abnormalities that are observed in prenatal diagnosis. Deletion in the distal region of 4p and 4q were generally present in ring chromosomal pathology of 4th chromosomes and terminal deletion in the 4p usually include Wolf–Hirschhorn Syndrome (WHS) critical region. In this study, it was aimed to determine the abnormal phenotypes of a prenatal diagnosis case with ring chromosome 4 in chromosome analysis by investigating with advanced molecular techniques. A 23 year old patient (gravida 1, para 0) referred for amniocynthesis due to abnormal maternal serum screening result in the 16th week of second pregnancy. Cytogenetic analysis of cultured amniyotic fluid cells revealed out ring chromosome 4. The karyotypes of both the mother and the father were normal. Fluorescence in situ hybridization(FISH) revealed terminal loss in both the 4p and 4q arms of ring chromosome 4. An further FISH research, however, found no loss in the WHS crucial area of both normal and ring chromosome 4 in both normal and ring chromosome 4. These results were confirmed by means of array-CGH showing terminal deletions on 4p16.3 (130 kb) and 4q35.2 (2.449 Mb). This is the first prenatal case of 4p and 4q subtelomeric deletion of ring chromosome 4 without the involvement of the WHS crucial region, according to our analysis of the literature.Our research describes a foetal instance with a ring chromosome 4 aberration that was completely described by array-CGH and offered comprehensive data for prenatal diagnosis genetic counselling.